The Impact of Covid-19 on the Resilience of Families of Parepare Nusantara Port Transport Workers: Islamic Marriage Law - Sri Harniati, Sri Harniati; Nasri Hamang, Nasri Hamang (Al-Iftah: Journal of Islamic studies and society, 2020)
This study discusses the impact of Covid-19 on the resilience of the families of port workers at Nusantara Parepare in the perspective of Islamic marriage law.With the problem of how the impact Covid-19 on the resilience of the families of Nusantara port transport workers in Parepare City. This type of study is a field study, namely a study that collects data directly from labor community informants. This study was conducted using a phenomenological approach. The results of this study indicate that 1) The impact of the Covid-19 pandemic has caused the economy of the port worker community to be increasingly difficult and deprived. At the time of the closure of the Nusantara port, many of the port workers' family conditions were not harmonious because their income was greatly reduced and decreased drastically;2) Condition family resilience due to the Covid-19 pandemic has greatly impacted port workers because the family's economy is increasingly depressed, making it very vulnerable to conflict in the family, and 3) The resilience and harmony of a family since the Covid-19 pandemic has led to disputes and conflicts due to the non-fulfillment of the necessities of life. And the families of port transport workers during the Covid-19 pandemic have become problematic families.